The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1542/peds.2022-057085
|View full text |Cite
|
Sign up to set email alerts
|

Relative Age and Psychotropic Drug Use in Preterm and Term-Born Children and Young Adults

Abstract: BACKGROUND AND OBJECTIVES: Being among the youngest within a school class is linked to disadvantages in various educational and mental health domains. This study aimed to investigate whether preterm born infants are particularly vulnerable to relative age effects on mental health, not previously studied. METHODS: We used registry data on all Norwegians born between 1989 and 1998 to compare prescription status for psychostimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Our main motivation was driven by targeted or precision pharmacovigilance, as certain QT-prolonging drugs, such as antipsychotics or drugs used to treat ADHD, are more commonly prescribed in former preterm subjects [ 10 , 11 ]. As these drugs are associated with prolongation of the QT c-Bazett interval, the absence of any a priori prolongation in former ELBW and/or preterm subjects matters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our main motivation was driven by targeted or precision pharmacovigilance, as certain QT-prolonging drugs, such as antipsychotics or drugs used to treat ADHD, are more commonly prescribed in former preterm subjects [ 10 , 11 ]. As these drugs are associated with prolongation of the QT c-Bazett interval, the absence of any a priori prolongation in former ELBW and/or preterm subjects matters.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, neither Gervais et al (Canada) nor Salaets et al (Belgium) confirmed these differences in former preterm subjects in young adulthood and late childhood to adolescence, respectively [ 8 , 9 ]. More clarity on the presence or absence of a difference in QT c-Bazett is relevant for precision pharmacovigilance, as certain QTc-prolonging drugs, such as antipsychotics or attention deficit and hyperactivity disorder (ADHD) drugs, are more commonly prescribed in former premature infants [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%